Peran Investasi Langsung terhadap Penciptaan Lapangan Kerja di Indonesia: Sebuah Sintesis Literatur - Naipospos, Kania Mayulina; Budiman, Muhammad Akbar (Jurnal Kajian Ekonomi dan Pembangunan, 2025)
Foreign Direct Investment (FDI) is important for economic growth and job creation in Indonesia. This article aims to analyze the contribution of foreign direct investment to employment, identify the factors that influence this relationship, identify the positive and negative impacts of foreign direct investment on job creation in Indonesia, as well as the challenges faced in attracting and utilizing this investment. The research method used is literature review, collecting and analyzing data from various relevant sources. The research results show that foreign direct investment not only opens up new jobs, but also brings technology and skills that can improve the quality of the local workforce. Foreign direct investment has been proven to contribute significantly in creating job opportunities through new projects, technology transfer and improving the quality of the workforce. However, challenges such as dependence on foreign companies and the potential for labor exploitation remain concerns. Supportive policies need to be formulated to maximize the benefits of foreign direct investment for society, especially in terms of creating quality jobs. It is hoped that these findings will become a reference for policy makers, business people and academics in formulating more effective economic development strategies.